Validation of fragility fractures in primary care electronic medical records: a population-based study - Martinez-Laguna, D; Soria-Castro, A; Carbonell-Abella, C; Orozco, P; Estrada-Laza, P; Nogues, X; Diez-Perez, A; Prieto-Alhambra, D (Springer Verlag, 2016)
Electronic medical records databases use validated lists of ICD (or other) codes to identify fractures. These, however, are not specific enough to disentangle traumatic from fragility fractures. We report on the proportion of fragility fractures identified amongst a random sample of coded fractures in SIDIAP, both overall and after stratification by fracture site.